2020
DOI: 10.3390/s20092458
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Fault Diagnosis Approach for Chillers Based on 1-D Convolutional Neural Network and Gated Recurrent Unit

Abstract: The safety of an Internet Data Center (IDC) is directly determined by the reliability and stability of its chiller system. Thus, combined with deep learning technology, an innovative hybrid fault diagnosis approach (1D-CNN_GRU) based on the time-series sequences is proposed in this study for the chiller system using 1-Dimensional Convolutional Neural Network (1D-CNN) and Gated Recurrent Unit (GRU). Firstly, 1D-CNN is applied to automatically extract the local abstract features of the sensor sequence data. Seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…• Whereas the classification accuracy results are similar with GRU and LSTM cells, GRUs have fewer trainable parameters [43], so they require less memory, and they train and execute faster than LSTMs. • As the transceiver directly provides the I/Q samples of the received signal, the use of this format at the model input is more efficient than the use of amplitude and phase information, the calculation of which involves additional computational overhead for the device.…”
Section: B Baseline Methodsmentioning
confidence: 93%
“…• Whereas the classification accuracy results are similar with GRU and LSTM cells, GRUs have fewer trainable parameters [43], so they require less memory, and they train and execute faster than LSTMs. • As the transceiver directly provides the I/Q samples of the received signal, the use of this format at the model input is more efficient than the use of amplitude and phase information, the calculation of which involves additional computational overhead for the device.…”
Section: B Baseline Methodsmentioning
confidence: 93%
“…Other works on time series data sets makes use of different architectures of CNNs, RNNs and attention. Chiller fault data sets have shown that one dimensional temporal convolutions have achieved good results [31]. While using two layers, LSTMs have also outperformed other forms of RNNs in detecting faulty conditions in chillers as well.…”
Section: Related Workmentioning
confidence: 99%
“…In [ 35 ], a hierarchical CNN-based FD method was proposed by Guo et al for performing a mechanical FD task. In [ 36 ], Wang et al proposed a 1-D CNN (1D-CNN)-based Hiller system fault diagnosis method that combines 1D-CNN and a gated recurrent unit to perform the fault identification task. In [ 37 ], a random oversampling-based CNN FD method was presented by Chen et al to handle fault confusing problems and is applied in avionics FD.…”
Section: Related Workmentioning
confidence: 99%
“…Deep learning (DL) learns features from big data [ 32 , 33 ] and avoids the complex processes stemming from handcrafted features. CNN is a powerful DL model for handling two-dimensional (2-D) images and has been used in FD research, such as mechanical systems FD [ 34 , 35 ], circuit systems FD [ 36 ], and avionics FD [ 37 ]. In FD applications, because raw data is often sampled in one-dimensional (1-D) format, researchers have turned to feature extraction operations that construct 2-D features for addressing FD problems using CNNs, such as sliding window [ 38 , 39 ], short time Fourier transform (STFT) [ 40 ], discrete wavelet transform (DWT) [ 41 , 42 ], and Hilbert–Huang transform (HHT) [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%